Analysis of Financial Distress Factors Using Survival Analysis - Sari, Shafira Deswita; Kristanti, Farida Titik (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2024)
If a company cannot pay its short-term liabilities and the possibility of bankruptcy exists, it is considered to be financially distressed. Two factors can cause a company to experience financial distress, namely internal factors and external factors. and external factors. Internal factors are used in the study is liquidity, activity, firm size, and capital structure and the external factor is inflation. The research population is in the property, real estate, and building construction sectors listed on the IDX in 2016-2022. Purposive sampling technique obtained 53 companies being sampled. Analysis technique used is the survival analysis technique using SPSS 25. The results simultan test explain that liquidity, activites, firm size, capital structure, and inflation are simultaneously impact of financial distress. The results of partial tests, liquidity, activities, and capital structure do not have a impact of financial distress. Company size and inflation have a important negative impact on financial distressed.